Beyond Gender Binaries: Understanding And Enhancing Rights For Transgender Individuals - Richa Chaudhary, Prof. (Dr.) Mandeep Kumar (European Economic Letters (EEL), 2025)
Gender identity, as a deeply personal yet socially constructed reality, has long been confined within the narrow binaries of male and female. For transgender individuals, this restriction translates into systemic exclusion, violence, and the denial of basic human rights. This research explores how Indian law, policy, and society have historically enforced these binaries and how recent developments, particularly after the NALSA v. Union of India (2014) judgment and the Transgender Persons (Protection of Rights) Act (2019), attempt to dismantle them. Drawing from legal precedents, empirical studies, and community-based insights, the paper situates the transgender struggle within broader discourses of equality, dignity, and justice. Using doctrinal and socio-legal analysis, the study engages with lived realities ranging from financial exclusion and social stigma to institutional discrimination in education, health, and employment. While India’s legislative framework has evolved toward inclusion, gaps persist in its implementation, with bureaucratic barriers and social prejudices continuing to undermine the spirit of constitutional equality. Comparative references to Argentina, Germany, and Nepal illustrate how other jurisdictions have embraced self-identification and affirmative protections as cornerstones of gender justice. The paper argues that moving beyond gender binaries is not merely a question of legal reform but of social transformation a shift from tolerance to acceptance, and from recognition to empowerment. It concludes by recommending policy and institutional interventions that center the agency, voice, and lived experience of transgender persons, making inclusion both substantive and sustainable.